The Influence of Artificial Intelligence Image for Product Advertisements (Case Study of Using Model Photos in Levi's Advertisements) - Widyo Harsanto, Prayanto; Udayana, Anak Agung Gede Bagus; Satuti, Kinanthi Raras (Mudra Jurnal Seni Budaya, 2025)
Initially, photographic works were a representation of reality that depicted facts and truth. However, with the presence of artificial intelligence imaging has shifted the concept underlying photography. Openly the company Levi Strauss & Co with its Levi's product uses photos of models generated by AI for its advertisements. The presence of artificial intelligence (AI) in the field of photography has become a dialectical discourse in society that can replace human work in various fields. This study aims to understand visual phenomena by describing and analyzing them to see the impact of Artificial Intelligence (AI) technology in the field of photography on Levi's advertisements. The focus of the research is the influence of technological advances on very significant changes in the world of advertising. Gillian Rose's Visual Methodology is used to present comprehensively, assisted by various literatures. Data collection is done by conducting observations, documentation, interviews, and questionnaires. The socio-technological approach is used to reveal the influence of technological developments on social issues and advertising photography phenomena as research objects. The results of the study show that artificial intelligence technology, namely, (1) produces more creative and innovative visual aesthetics for advertising; (2) supports more effective and efficient work; (3) there is social anxiety for some commercial photographers, designers and advertising models.